Zakat collection institution - Sholeha, Zumaroh Nur (Maliki Interdisciplinary Journal, 2025)
The Lembaga amil zakat (LAZ) is an important organization that helps to increase and improve zakat as well as analyze its effectiveness and the challenges it faces in Indonesian zakat administration. The methodology used in this study is a kualitatif approach using literary analysis and the belief that LAZ has a significant impact on the economy of the general public through zakat-based productive programs such as microbusiness bantuan, education beasiswa, and health services. However, factors such as transparasi kurangnya, societal trust, and suboptimal regulations continue to be obstacles to optimizing LAZ. Due to this, it is necessary to increase tata Kelola, use digital innovations in zakat administration, and collaborate with the government and LAZ to increase the effectiveness and reliability of this organization in zakat administration in a professional and thorough manner.